REKONSTRUKSI EPISTEMOLOGI PENDIDIKAN ISLAM : ANALISIS KOMPARATIF KEBIJAKAN DAN KURIKULUM DI INDONESIA, MALAYSIA DAN TURKI - Dede Misbahul Alam; Dindin; Syarif Hidayatullah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic education in the contemporary era faces the challenge of dualism between revelation-based education and science-based education. This research aims to comparatively dissect the models of Islamic education in three countries with distinct socio-political characteristics: Indonesia, Malaysia, and Turkey. The primary issue addressed is how curriculum integration is implemented and to what extent state authority influences the independence of Islamic educational institutions. The research method employed is qualitative with a descriptive comparative study approach through library research data collection techniques. The findings indicate that Indonesia implements a pluralistic-decentralized model through the dichotomy of Madrasahs and Integrated Islamic Schools; Malaysia applies an integrative-centralized model that rigidly incorporates religious education into the national curriculum; while Turkey utilizes a functionalist model through Imam Hatip Schools that bridge Islamic values within a secular state framework. The conclusion of this study asserts that the success of Islamic education in various countries is determined not only by curricular content but also by the system's ability to adapt to political policies and global labor market demands.